Model Komunikasi dan Jenis-Jenisnya - Hotmayjar Ardila Dalimunthe (Al-Balagh : Jurnal Komunikasi Islam, 2022)
This study aims to find a model of communication and its types, it is equally known that if humans as individual beings and social beings, have the urge to know, want to progress and develop, then one of the means is communication. Therefore communication is a necessity absolute for human life. This study uses the library research method by using descriptive analysis and combining all the information needed by researchers. The findings in this study are related to the model in communication interpreted as a visual explanation using lines and pictures to explain the various components and processes of communication. The communication model serves as a means to explain, predict and also measure phenomena. There are various models in communication but in general the models in communication are divided into three perspectives, namely the linear model, the interactional model and the transactional model. By understanding the model in communication can help individuals in maximizing the function of communication, minimizing failures in communication and also developing the science of communication